Plastic Bronchitis in Children: A Review of 55 Cases over a 10-Year Period - Xiaowen Chen; Shangzhi Wu; Zhanhang Huang; Yuneng Lin; Jiaxing Xu; Qingyun Xu; Dehui Chen (International Journal of Pediatrics)
Objective. To summarize the clinical characteristics and treatment experiences of patients with plastic bronchitis (PB). Methods. All patients who were diagnosed with PB by bronchoscopic removal of tree-like casts at a single institution from January 2012 to May 2022 were retrospectively reviewed. Demographic and clinical data were retrieved from electronic patient records. Results. A total of 55 patients, with a median age of 5.3 years, were eligible for the study. Nineteen cases had underlying diseases, among which asthma was the most common. The median course of the disease before admission was 11 days. Clinical symptoms were characterized by cough and fever, while moist rales (78.2%) and dyspnea (61.8%) were the most common signs. The most common laboratory finding was elevated C-reactive protein (58.2%). Patchy opacity was the most frequent radiographic finding (81.2%), followed by consolidation (60.0%) and pleural effusion (43.6%). Respiratory pathogens were detected in 41 cases, and M. pneumoniae was the most common one (41.8%), followed by adenovirus (20.0%) and influenza B virus (10.9%). The casts were removed by alveolar lavage, combined with ambroxol immersion (63.6%) and forceps (30.9%). Patients received an average of 2.3 bronchoscopies, and the median time for the first procedure was 3 days after admission. Antibiotics were given to all patients, methylprednisolone to 33 (60.0%), and gamma globulin to 25 (45.5%). A total of 53 cases were improved with an overall mortality rate of 3.6%. Conclusions. PB in children is characterized by airway obstruction, mostly caused by respiratory infections, and timely removal of the cast by bronchoscopy is the most effective treatment.